ANALISIS PENERAPAN BRAND IMAGE PADA PRODUK BULOG DI PERUM BULOG DIVRE SULSELBAR DI MAKASSAR - khaidir ahmad; Abdul Muttalib; M Hidayat (Jurnal Ilmu Manajemen Profitability, 2019)
Kheidir Ahmad, 2018. Analysis of the application of brand image to Bulog products at the Regional Division of Divre Sulselbar Bulog. Thesis Management Study Program, Faculty of Economics and Business, University of Muhammadiyah Makassar. Supervised by Advisor I Abdul Muttalib and Advisor II M. Hidayat. This study aims to assess the application of brand image to Bulog products at the Regional Division of Divre Sulselbar Bulog. The type of research used in this research is qualitative descriptive research. The data in this study were obtained using in-depth interview techniques and direct observation techniques. The in-depth interview technique was conducted on 1 key informant and 3 non-key informants. The observation technique was carried out by researchers on the brand image of Bulog products. The results of this study indicate that the products at the Bulog Divre Sulselbar Corporation in the application of brand image apply three things, namely, the Favor Ability of Brand Association in the form of price, design, benefits and experience of brand image. Strength of Brand Association in the form of brand uniqueness, brand strength and positive attitude applied in brand image. Uniqueness of brand associations in the form of logos, advertisements, and customers respond to Bulog's product brand. Perum Bulog Divre Sulselbar has implemented a brand image on every product produced by Bulog.